Comparative analysis between three methods of bone estimating age in individuals with down syndrome by mode of the hand and wrist ray - dos Santos, Luis Roque de Araújo [UNESP]; Castilho, Júlio Cezar de Melo [UNESP]; Pinto, Shelon Cristina Souza; Borges, Alvaro Henrique; Tonetto, Mateus Rodrigues; Lima, Darlon Martins; Bandéca, Matheus Coelho; da Silva, Marcos André dos Santos (Jaypee Brothers Medical Publishing, 2013)
The wrist and hand region has been the most commonly used for estimating age and osseous development due to the great number of ossification centers. The aim was to determine which method, Tanner & Whitehouse's (TW3), Greulich & Pyle's (GP) or Eklof & Ringertz's, more closely relates to the chronological age in subjects with Down syndrome with chronological ages between 61 and 180 months, using wrist and hand radiographs. The sample consisted of 85 radiographs, 52 of males and 33 of females. Eklof & Ringertz's method was computerized (Radiomemory). Greulich & Pyle's atlas was used and compared with the wrist and hand radiographs. For the TW3 method, 13 ossification centers were evaluated; for each one of them, there are seven or eight development stages to which scores are assigned; these scores are then added and the results are transformed into osseous age values. No statistically significant differences were observed between the male and female genders for methods TW3 and GP, contrasting with the observed differences for the Eklof & Ringertz method. Correlation (r2) between osseous and chronological ages was 0.8262 for TW3 and 0.7965 for GP, while for the method of Eklof & Ringertz, it was 0.7656 for females and 0.8353 for males. The author concluded that the osseous age assessment method that better related to the chronological age was the TW3, followed by Greulich & Pyle's and Eklof & Ringertz's.
Keywords: Age determination by skeleton; Bone development; Down syndrome; Hand; Hand bones; Radiography; Wrist; adolescent; age; age determination; bone development; carpal bone; child; female; growth, development and aging; hand bone; human; image processing; male; methodology; pathophysiology; physiology; preschool child; radiography; radius; ulna; Adolescent; Age Determination by Skeleton; Age Factors; Bone Development; Carpal Bones; Child; Child, Preschool; Down Syndrome; Female; Hand Bones; Humans; Image Processing, Computer-Assisted; Male; Osteogenesis; Radius; Ulna